Plataformas educativas digitales en el proceso enseñanza – aprendizaje - Freire Guzmán, Andrea Nicole (2022)
The technology evolution has generated an impact into educational scope, consequently, the digital educational platforms inclusion within teaching-learning process is required by teachers and students, since it has a favorable repositories and tools services wide range, to the virtual environment development for significant learning from student, which it is so the platforms derive as an alternative for a paradigm that creates a pedagogical environment new vision. Before, the educators training ignorance and lack in front of digital educational platforms, which were incorporated by educational institutions, there remains the possibility that the virtual environment does not correspond to didactic process that the teacher and student need for interaction, motivation, diversity and academic knowledge. Thus, the project aim is to propose the digital educational platforms use such as: Moodle, Google Classroom and Microsoft Teams for Basic General Education student teaching-learning process strengthening from "Manuela Iturralde" Educational Unit, Cotopaxi province, Latacunga canton, Taniloma parish. The used methodology is based onto interpretive paradigm, since according to its conception, it allowed to make a reflection of information and communication technology use (Tic) into teaching-learning process. The project is related with the qualitative research type, because it was used to deepen the tools management, which offered by digital educational platforms into developed pedagogical practice four stages: preparatory, field work, analytical and informative - proposal. Finally, the method, which directs the research is the inductive, because it allowed to get clues against the teacher reality with the educational platforms use into the didactic process to reach a conclusion about the made study, using the interview technique the teacher Basic General Education, where it is applied interview guide instrument to the teacher. The result is a training workshop directed to teachers about three digital educational platforms use oriented to the teaching and learning process, by contextualizing each them with graphic presentations, likewise, there is an instructive, through triptychs as a access guide the respective accounts, finally, the teacher participation activities elaboration for feedback, what has been learned. This project contributes to strengthen the didactic process into Basic General Education, by using technological resources for an educational space creation with rousing interest purpose by learning different way in the student, developing abilities and skills present into boys and girls at the use technology by education.